Differences in Language Conversation Use by Gender - kristy, Intan melina (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2022)
The main thing that affects language is Gender, it can affect the choice of words used. Then the language used by women is different from the language used by men. Those state that the choices of words, vocabulary, or sentences of language conversation through gender are different. This study conducted to analyze what happened or was experienced by certain groups which focused on the differences in the use of spoken language that were studied by gender. There are no participants in this research because this research use library research which is based on the literature review to analyze the data. This research uses descriptive qualitative. Analyzing and collecting data conducted by compiling or clarifying and interpreting. Data were collected through analyzing and reviewing sources in the form of books and articles discussing the topic then analyze the data in order to draw the conclusion. The result of study found that the language differences exist because of the paradigm social then produce differences in language conversation such as vocabulary use, word choice and emotional differences.